PEMBENTUKAN STRUKTUR MIKRO DAN SIFAT MAGNETIK Sm2Co17 MELALUI CARA SINTERING - Siahaan, Mabe (Indonesian Journal of Aerospace, 2007)
The studies, observation of microstructure and magnetic coercivity of the permanent magnet sample have been done through a metallurgy powders technique preparation process. The raw materials with the composition of Sm (Co, Cu, Fe, Zr)z equal 8.5 (at percent) initially in the form of powders alloys with the mean particle size of was 20-30 um. This powder is compacted through one direction pressed in the dies and the following with heat treatment steps. After sintering steps and homogeneity of each at a temperatures of 1190 degree celcius and 1130 degree celcius, the solid sample achieved with Sm2Co17 is mainly the magnetics phase. Further heat treatment that their received the next 10 degree celcius/minute until room temperature. And have succeeded to form cellular structures on the matrixs of magnetics phases while other phases in the form cellular structures on the matrixs of magnetics phases while other phases in the form of grain boundary and the magnetics coercivity. Conclution from result of this study is compared with the result of former research.